Place Of Earth Faults In Geology And Main Tectonophysical Indicators - Dononov Jasur Ural o‘g‘li; Amirov Abbos Rustamovich (Genius Journals, 2025)
It is difficult to limit the place of earth cracks in geology, no matter how high it is appreciated. It plays a key role in the formation of mineral deposits. Whether minerals are solid (gold, copper, aluminum, etc.), liquid or gaseous (groundwater, oil and gas), affects their location and migration. The structure of the geological environment, the course of the processes taking place in it, the increase or decrease in the amount of stress and deformation depend on the morphology, density and other parameters of the earth's cracks. Even the formation of earthquake foci is related to cracks. Therefore, the study of cracks is of great importance not only in mining and seismology, but also for solid construction - in the correct implementation of the engineering-geological conditions.
Keywords: Lithosphere; mantle; Tavoksoy